2002
DOI: 10.1097/00006123-200206000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of the Medial Pectoral Nerve: Myth or Reality?

Abstract: Our surgical results suggest that the transfer of the medial pectoral nerve to the musculocutaneous nerve and also to the axillary nerve may be a reliable and effective procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 8 publications
1
52
0
3
Order By: Relevance
“…9 We graded shoulder function using the system described by Samardzic et al 10,11 To evaluate shoulder abduction, the patients were asked to abduct and externally rotate their shoulders. We recorded muscle strength and the degree of shoulder abduction and external rotation.…”
Section: Outcome Assessmentmentioning
confidence: 99%
“…9 We graded shoulder function using the system described by Samardzic et al 10,11 To evaluate shoulder abduction, the patients were asked to abduct and externally rotate their shoulders. We recorded muscle strength and the degree of shoulder abduction and external rotation.…”
Section: Outcome Assessmentmentioning
confidence: 99%
“…As reported in prior clinical studies, we found that the pectoral nerves reached the axillary nerve without nerve graft and without cutting the ansa pectoralis in all cases. 13,18 However, when 1 branch of the pectoral nerves is transferred to the axillary nerve, a diameter disparity should be expected. An adequate length of the middle and the inferior branches was found to reach the suprascapular nerve without nerve grafting and without cutting the ansa pectoralis.…”
Section: Discussionmentioning
confidence: 99%
“…13,18 Samardzic reported that useful functional recovery was achieved in 9 of 11 patients who had medial pectoral nerve transfer to the axillary nerve. 18 Moreover, Stockinger obtained M4 shoulder abduction by transferring a medial pectoral nerve to an axillary nerve in 1 patient. 13 The pectoral nerves are intraplexal, voluntary motor nerves with a high number of motor fibers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…82,83 Acceptable results can also be obtained with transfers of the thoracodorsal nerve 84,85 and branches of the medial pectoral nerve. 86,87 Shoulder results have not had the same success, even though the suprascapular and axillary nerves are reinnervated simultaneously. 88 Donor branches are traditionally harvested from the triceps muscle and the accessory nerve.…”
Section: Nerve Transfersmentioning
confidence: 99%